Thrombomodulin/thrombin系で産生されるTAFIa/carboxypeptidase Bは補体成分C5aを不活性化することでoxaliplatin誘発性末梢神経障害を抑制する - 南, 達郎; 坪田, 真帆; 川畑, 篤史; 圓尾, 賢悟; 関口, 富美子; 伊藤, 彰敏; 田島, 和樹; 西堀, 正洋 (日本薬理学会年会要旨集, 2022)
Prevention of oxaliplatin-induced peripheral neuropathy (OIPN) by thrombomodulin alfa (TMα) involves thrombin-dependent activation of thrombin-activatable fibrinolysis inhibitor (TAFI) and protein C (PC), in addition to inactivation of high mobility group box 1 (HMGB1). We thus analyzed the anti-OIPN effects of activated forms of TAFI (TAFIa), known as carboxypeptidase B (CPB), and PC (APC) in mice. OIPN was inhibited by TMα, an anti-HMGB1-neutralizing antibody (HAb) or TAFIa/CPB, and partially by APC. Combination of HAb with APC, but not TAFIa/CPB, at subeffective doses abolished OIPN. TAFIa/CPB at a subeffective dose in combination with APC at a maximal dose also abolished OIPN. Intraplantar (i.pl.) HMGB1-induced allodynia was inhibited by TMα, but not APC or TAFIa/CPB. TAFIa/CPB abolished the allodynia following i.pl. C5a, a complement component, and bradykinin, known to be degraded by TAFIa/CPB. The C5a-induced allodynia was also inhibited by HAb as well as a C5aR antagonist. The C5aR antagonist, but not combination of B1 and B2 antagonists, abolished OIPN. Our study ascertains that thrombin-dependent degradation of HMGB1 and generation of  APC and TAFIa/CPB by TMα are necessary to abolish OIPN, and provides novel evidence that C5a targeted by TAFIa/CPB contributes to the development of OIPN via HMGB1-dependent mechanisms.